2022
DOI: 10.3892/ol.2022.13270
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of competitive endogenous RNAs network: Identification and validation of prediction model composed of mRNA signature and miRNA signature in gastric cancer

Abstract: Gastric cancer (GC), one of the most lethal malignant tumors, is highly aggressive with a poor prognosis, while the molecular mechanisms underlying it remain largely unknown. Although advanced imaging techniques and comprehensive treatment facilitate the diagnosis and survival of some GC patients, the precise diagnosis and prognosis are still a challenge. The present study used publicly available gene expression profiles from The Cancer Genome Atlas and Gene Expression Omnibus datasets including mRNA, micro (m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Li et.al showed that miR-6512 downregulated in gastric cancer patients and seems to have a correlation with skin manifestations and fibrosis 46 . Moreover, a study by Ding demonstrated that miR-6507 was among top five down expressed miRNAs in GC and may serve as a good predictive biomarker 47 . Another study introduced miR-6510 as a potential prognostic biomarker in GC patients 48 .…”
Section: Discussionmentioning
confidence: 99%
“…Li et.al showed that miR-6512 downregulated in gastric cancer patients and seems to have a correlation with skin manifestations and fibrosis 46 . Moreover, a study by Ding demonstrated that miR-6507 was among top five down expressed miRNAs in GC and may serve as a good predictive biomarker 47 . Another study introduced miR-6510 as a potential prognostic biomarker in GC patients 48 .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, an increasing number of molecular biomarkers have been integrated into models for the prognostic assessment of cancer patients. [4–8] However, the prognostic features and nomographs of multiple mRNA in TSCC patients have not been sufficiently explored.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, an increasing number of molecular biomarkers have been integrated into models for the prognostic assessment of cancer patients. [4][5][6][7][8] However, the prognostic features and nomographs With the development of second-generation sequencing technology, attention has gradually turned to the analysis and alignment of high-throughput sequencing data, leading to the establishment of The Cancer Genome Atlas (TCGA) database, which provides an avenue for tumor-related research through the mining and analysis of genomic data on cancer genes. Initiated and completed by the National Cancer Institute and the National Human Genome Research Institute in the United States, TCGA is a genomic variation map of human tumors obtained through large-scale sequencing of the human tumor genome, containing information on genomics, transcriptomics, epigenetics, proteomics, as well as clinical information.…”
Section: Introductionmentioning
confidence: 99%